Analisis Kemampuan Daya Beli Dan Kesejahteraan Masyarakat Terhadap Dampak Kenaikan Ppn 12% - Renani, Heni; Mareta Rizal, Ebil; Wati Keristin, Usnia (Politeknik Raflesia Press, 2025)
The Indonesian government has implemented a Value Added Tax (VAT) increase to 12% starting in January 2025, in accordance with Law No. 7 of 2021 on Tax Regulation Harmonization. Previously, the VAT rate increased from 10% to 11% in April 2022. The 12% VAT is applied to luxury goods and services, such as exclusive vehicles and high-value properties, which are generally consumed by the upper-middle-class economic group. This study analyzes the impact of the VAT increase on the upper-middle-class society using a quantitative approach and incidental data selection technique. A sample of 100 respondents was calculated using Slovin's formula from the population of workers aged 18 years and above. Data analysis was conducted through multiple linear regression using SPSS, including t-test, F-test, and coefficient of determination test. The results show that purchasing power has a positive but insignificant effect on the VAT increase, as the tax only applies to luxury goods, while basic needs remain VAT-exempt. On the other hand, societal welfare has a significant impact, where the VAT increase may reduce GDP and increase the number of poor people due to inflation. The coefficient of determination indicates that purchasing power and welfare variables explain 95.9% of the variation in the VAT increase. The implications of this study emphasize the need for compensation policies to mitigate the economic impact on vulnerable groups. The government should consider tax incentives or subsidies to maintain welfare and purchasing power stability. This study is expected to serve as a reference for policymakers in formulating more inclusive fiscal policies that comprehensively consider socio-economic impacts.